Cash versus Kind, Self-selection, and Efficient Transfers - Blackorby, Charles; Donaldson, David (American Economic Review, 1988)
This paper investigates second-best (transfers in kind) and third-best (subsidies and taxes) Pare to optima in a simple model were government lacks full information ab out consumer types (who is able, who is infirm). These Pareto optima rely on self-selection. The authors show that those second-best Paret o optima which are not also first-best (some do exist) can only be su pported by rationing. They also show that every third-best optimum, o ther than the equal-income Walrasian equilibrium, is Pareto-dominated by some second-best optimum. In addition, standard "willingness-to- pay" cost-benefit tests are inappropriate in this environment. Copyright 1988 by American Economic Association.